A lakókörnyezeti biztonságérzet településtípusok szerinti különbsége Magyarországon - Dusek, Tamás (Közép-Európai Közlemények, 2015)
This study examines the association between urban/rural residence and the perceived neighbourhood safety in Hungary. The main component in the neighborhood satisfaction is the subjective evaluation of safety. One obvious finding of previous research is that the best predictor of fear of crime is sex, at least from the socio-demographic variables. In our research the spatial aspect was more important: the spatial differences overshadow the gender differences, in spite of the high level of spatial aggregation.